MAZHAB PEMIKIRAN EKONOMI ISLAM KONTEMPORER - Sulaiman, Sofyan (Fakultas Syariah Institut Agama Islam Negeri Palu, 2019)
Since the 1970s, studies of the Islamic economy have developed rapidly. Various topics around Islamic economics are discussed, ranging from Islamic economic philosophy, Islamic economic system, Islamic criticism of conventional economics, Islamic economic history and thought, to the Islamic financial system. There are several factors that encourage the development of Islamic economic scholarship, some of them are: personal motivation to promote Islamic economics, sponsorship from academic and non-academic institutions as well as organizations, Muslim societies, Muslim student associations, and also the dedication of publishers. As time goes by, Islamic economics bears many figures with various Islamic economic schools. According to the writer's findings there are at least five schools of contemporary Islamic economic thought, they are (1) Baqir al-Sadr, (2) Mainstream, (3) Alternatives, (4) Hamfara, and (5) Murabitun.